Removal of organic pollutants from water using carbon nanotubes functionalized with deep eutectic solvents / Rusul Khaleel Ibrahim - Rusul Khaleel , Ibrahim (2018)
Many industries discharge large amount of wastewater that constitute the attention of many environmental concerns because it contains toxic and persistent organic pollutants that pollute the nature and threaten the human health. Although, carbon nanotubes (CNTs) have a high adsorption capacity for the removal of various kinds of organic pollutants from water, many flaws are hindering their adsorption performance. Functionalization of CNTs is a decisive process to overcome all the restrictions of CNTs application and to increase their removal efficiency. Therefore, this research has been carried out to investigate the potential of deep eutectic solvents (DESs) as novel functionalization agents for carbon nanotubes (CNTs) which can open a new window of opportunity in the area of wastewater treatment. In this regard, ten DESs were synthesized using five different salts and two hydrogen bond donors (HBDs) (i.e. ethylene glycol and di-ethylene glycol). Various molar ratios of HBD to salts were prepared to determine the optimum molar ratio by which the DES is homogeneous and stable. The DESs freezing points and functional groups were investigated, in addition to their physical properties of viscosity, density, conductivity and surface tension were determined as function of temperature in the particular temperature range of 293.15- 353.15 K. It is worth mentioning that all examined DESs were stable and in liquid phase at room temperature which emphasize their promising potential to be utilized as inexpensive environment-friendlier solvents. Owing to their low recorded freezing points and viscosities, DESs can be effortlessly processed without any further heating required. Subsequently, the prepared DESs were used to functionalize CNTs and produce novel adsorbents for the removal of 2,4-dichlorophenol (2,4-DCP) and methylene orange (MO) from water. A primary screening of adsorption process was conducted, and the chemical, physical and morphological properties of the adsorbents with the highest removal efficiencies were investigated using RAMAN, FTIR, FESEM, zeta potential, TGA and BET surface area. The effect of DES was obvious by increasing the purity and the surface area of CNTs resulting in increasing the maximum adsorption capacity of CNTs for 2,4-DCP and MO removal to reach 290 mg/g and 224 mg/g, respectively. Adsorption studies were carried out to evaluate the optimum conditions, kinetics and isotherms for 2,4-DCP adsorption process. RSM-CCD experimental design was used to conduct the optimization studies and to determine the optimum conditions for 2,4-DCP and MO removal by each selected adsorbent individually. Furthermore, all experimental data fitted well the pseudo-second order kinetic model and the equilibrium data for all DES-functionalized adsorbents was well fitted by both Langmuir and Freundlich isotherm models.